Policy Inconsistency between Science and Technology Promotion and Graduate Education Regarding Developing Researchers with Science Communication Skills in Japan. Issue 1 (2nd January 2021) - Ishihara-Shineha, Seiko
Abstract: Japan, like other countries, recognizes the need to shift the focus of the public communication of science and technology from science literacy via one-way communication to the public engagement of science and technology via dialogue. During the shift of perspectives, Japanese science policy tried to encourage science communication (SC) by cultivating the professional science communicator and communication capacity of scientists. This study aims to analyze the structural issues of developing science communication, particularly focusing on the gap between science policy and graduate education (GE) policy concerning the human resource development of scientists. The analyses found a lack of science communication development in graduate education policies, despite the emphasis on this in government science and technology (ST) policies. Simultaneously, it showed that there are few training courses for science communication and job recruiting for academic institutions. Discussions for systematic implementation of SC training in the GE system are expected to bridge higher education and ST policies.